Analisa Kualitas Tanah Pada Berbagai Penggunaan Lahan di Sub Sub DAS Cimanuk Hulu - Nurina Hanum Ayuningtias; Mahfud Arifin; Maya Damayani (Fakultas Pertanian Universitas Padjadjaran, 2016)
Soil quality test is needed to find out the influence of landuse change due to soil quality dan characteristics. This research aims to comparing various land use that influence the physical, chemical and biological soil on Andisol and Inceptisol, obtain information of soil quality at various land uses on Andisol and Inceptisol, and study the relationship between soil quality and erosion at various land use The study was conducted in Sub Sub watershed Hulu Cimanuk with an area of 16.171 hectares. The study was conducted on four different types of land use namely forest land, agriculture land, tea garden and mixed garden. The study was conducted with survey methods, descriptive and comparative. Erosion calculation using the RUSLE formula.Analysis of soil quality is calculated based on criteria Mausbach & Seybold (1998) and modified in accordance with the conditions of the study area. The results showed that each land use has a different effect on soils quality nor with erosion. Soil quality on forest land has higher value than other land use and erosion that occurs most low at 0.2 tonnes / ha / year. The use of dry land has the lowest value of soil erosion begitupula highest of 387 tonnes / ha / year.Key words: erosion, landuse change, soil quality, and watershed.